Theoretical Prediction on [5]Radialene Sandwich Complexes (CpM) 2 (C 10 H 10 ) (Cp = η 5 -C 5 H 5 ; M = Fe, Co, Ni): Geometry, Spin States, and Bonding - Liu, Nan-Nan; Xue, Ying-Ying; Ding, Yi-Hong (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2017)
[5]Radialene, the missing link for synthesis of radialene family, has been finally obtained via the preparation and decomplexation of the [5]radialene-bis-Fe(CO) complex. The stability of [5]radialene complex benefits from the coordination with Fe(CO) by losing free 1,3-butadiene structures to avoid polymerization. In light of the similar coordination ability of half-sandwiches CpM(Cp = η -C H ; M = Fe, Co, Ni), there is a great possibility that the sandwiched complexes of [5]radialene with CpM are available. Herein, we present the first theoretical prediction on the geometry, spin states and bonding of (CpM)(C H ) and (CpM) (C H ). For M = Fe, Co, Ni, the ground states of (CpM)(C H ) and (CpM) (C H ) are doublet and triplet, singlet and singlet, and doublet and triplet states, where each Fe, Co, and Ni adopts 17, 18, and 19 electron-configuration, respectively. In particular, (CpFe) (C H ) and (CpNi) (C H ) have considerable open-shell singlet features. Generally the trans isomers of (CpM) (C H ) with two CpM fragments on the opposite sides of the [5]radialene plane are apparently more stable than the cis ones with CpM fragments on the same side. However, for the singlet and triplet isomers of (CpNi) (C H ) (both cis and trans isomers), the energy differences are relatively small, indicating that these isomers all have the opportunity to exist. Besides, the easy Diels-Alder (DA) dimerization between the [3]dendralene-like fragments of (CpM)(C H ) suggests the great difficulty in isolating the (CpM)(C H ) monomer.